Applying the PhET Simulation and Problem-Based Learning to Enhance Students' Problem-Solving Ability - Jaswadi Jaswadi; Windy Zaerani; Solihin Rohmat; Aeruni; Fahmi Ilham (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
The primary focus of physics instruction in schools is to improve students' problem-solving skills. This study aims to determine whether employing problem-based learning can enhance students' problem-solving skills. This study employs a quasi-experimental design with a non-equivalent control group. It was discovered that students' problem-solving skills remained deficient due to less collaborative and active learning. The study was carried out in classes XI A through XI D at MAN 1 Mataram. The researchers used purposive sampling, which resulted in XI C and XI D being designated as the experimental and control classes, respectively. The test used in the research data collection method consisted of ten questions. Pretest and posttest results are research data. NGain is used to evaluate the effectiveness of the learning process. According to the N-Gain results, the N-Gain of the experimental class was 0,66, whereas the control class was 0,48. Therefore, it can be said that using PhET simulations to facilitate problem-based learning is a good way to enhance problem-solving abilities. Compared to traditional learning, the use of the problem-based learning paradigm with PhET simulation is more successful.